Factors influencing the effectiveness of remote patient monitoring interventions: a realist review - Monica L Taylor; Emma E Thomas; Centaine L Snoswell; Anthony C Smith; Liam J Caffery; Annie Banbury; Helen M Haydon; Victor M Gallegos Rejas (BMJ Open)
Objectives Our recent systematic review determined that remote patient monitoring (RPM) interventions can reduce acute care use. However, effectiveness varied within and between populations. Clinicians, researchers, and policymakers require more than evidence of effect; they need guidance on how best to design and implement RPM interventions. Therefore, this study aimed to explore these results further to (1) identify factors of RPM interventions that relate to increased and decreased acute care use and (2) develop recommendations for future RPM interventions.Design Realist review—a qualitative systematic review method which aims to identify and explain why intervention results vary in different situations. We analysed secondarily 91 studies included in our previous systematic review that reported on RPM interventions and the impact on acute care use. Online databases PubMed, EMBASE and CINAHL were searched in October 2020. Included studies were published in English during 2015–2020 and used RPM to monitor an individual’s biometric data (eg, heart rate, blood pressure) from a distance.Primary and secondary outcome measures Contextual factors and potential mechanisms that led to variation in acute care use (hospitalisations, length of stay or emergency department presentations).Results Across a range of RPM interventions 31 factors emerged that impact the effectiveness of RPM innovations on acute care use. These were synthesised into six theories of intervention success: (1) targeting populations at high risk; (2) accurately detecting a decline in health; (3) providing responsive and timely care; (4) personalising care; (5) enhancing self-management, and (6) ensuring collaborative and coordinated care.Conclusion While RPM interventions are complex, if they are designed with patients, providers and the implementation setting in mind and incorporate the key variables identified within this review, it is more likely that they will be effective at reducing acute hospital events.PROSPERO registration number CRD42020142523.